Climatic and environmental factors matter for internal European net migration: a panel regression analysis of 19 European countries from 2004 to 2019 - Link, Ann-Christine; Brenner, Thomas (Regional environmental change, 2026)
This study contributes to European migration research by exploring the connections between climatic and environmental factors and internal net migration rates—a subject of growing interest in political, academic, and public realms. Existing studies have primarily focused on the Global South or, within Europe, on the Mediterranean region, with an emphasis on exploring climatic impacts on international migration. This research uniquely concentrates on internal migration within 19 European countries from 2004 to 2019, utilizing municipalities as observations. Employing panel regressions, we comprehensively assess the relationship between internal net migration and 39 variations of climatic (sunshine, temperature, precipitation) and environmental factors (pollutants, discharge, vegetation, wildfires) while controlling for economic drivers. We found that climatic and environmental factors contribute to explaining internal net migration patterns in Europe, with strong differences at the region and country levels. Climatic and environmental factors have the highest explanatory power in Southern Europe, but also matter in other regions and countries. Our findings support the notion of amenity migration, where Europeans aim to increase the quality of life by moving towards favorable and away from unfavorable climatic and environmental amenities. Consequently, our results emphasize the importance of recognizing climate- and environment-related migration as a present reality within Europe and should not be regarded as a distant or external issue. This recognition is crucial to ensure that human (im)mobilities under climatic and environmental change are voluntary and adaptive, rather than becoming forced or maladaptive.
Gesehen am 20.01.2026